Biomarcadores en artritis reumatoidea: importancia y valor diagnóstico en la práctica clínica - Mora Rodríguez, Cristhian Emanuel (Machala : Universidad Técnica de Machala, 2019)
Introduction: rheumatoid arthritis (RA) is a chronic inflammatory symmetric, destructive and sometimes multisystemic polyarthritis caused by the formation of pannus (inflammatory synovial tissue) thus invading the cartilage and bone, which without immediate treatment facilitates bone destruction by driving in this way to irreversible disability. Objective: To determine the importance of biomarkers and their usefulness in the diagnosis of rheumatoid arthritis. Methods: a bibliographical review was made in the PubMed, ScienceDirect and Google Academic database in the time from January 2013 to January 2019, with the key terms in English rheumatoid arthritis, biomarkers, antibodies and diagnosis, as well as texts doctors that contain information on rheumatoid arthritis, biomarkers and diagnosis in English and Spanish. Results: the scientific articles indexed in high impact factor magazine and with the best levels of evidence according to the Scimago system were selected and articles that were not related to our review objective such as clinical manifestations and arthritis treatment were excluded. Rheumatoid. Conclusions: Biomarkers are important in clinical management in the different phases of Rheumatoid Arthritis because they have been shown to help predict disease progression, improve diagnosis and even determine prognosis.
Introducción: artritis reumatoide (AR) es una poliartritis inflamatoria crónica, simétrica, destructiva y en ocasiones multisistémica provocada por la formación de pannus (tejido sinovial inflamatorio) invadiendo de esta manera el cartílago y hueso, el cual sin tratamiento inmediato facilita la destrucción ósea conduciendo de esta manera a la discapacidad irreversible. Objetivo: Determinar la importancia de los biomarcadores y su utilidad para el diagnóstico de artritis reumatoide. Métodos: se realizó una revisión bibliográfica en la base de datos de PubMed, ScienceDirect y Google Académico en el tiempo comprendido desde enero del 2013 hasta enero del 2019, con los términos claves en ingles rheumatoid arthritis, biomarkers, and diagnosis, además de textos médicos que contengan información sobre artritis reumatoide, biomarcadores y diagnóstico en inglés y español. Resultados: se seleccionaron los artículos científicos indexadas en revista de alto factor de impacto y con los mejores niveles de evidencia según el sistema Scimago y se excluyeron artículos que no estaban relacionados con nuestro objetivo de revisión como es el caso de manifestaciones clínicas y tratamiento en artritis reumatoide. Conclusiones: Los biomarcadores son importantes en el manejo clínico en las distintas fases de la Artritis Reumatoide porque se ha demostrado que ayudan a predecir el progreso enfermedad, mejorar el diagnóstico e inclusive determinar el pronóstico.
Keywords: ARTRITIS REUMATOIDEA; BIOMARCADORES; DIAGNOSTICO; FACTOR REUMATOIDE